Geochronology, geochemistry, and zircon Hf isotopic compositions of Mesozoic intermediate-felsic intrusions in central Tibet: Petrogenetic and tectonic implications - Li, J.; Qin, K.; Li, G.; Richards, J.; Zhao, J.; Cao, Mingjian (Elsevier BV, 2014)
Mesozoic intermediate-felsic intrusions are widely distributed in the southern Qiangtang terrane, central Tibet. Zircon U-Pb dating shows that these intrusions formed in two periods in the Jurassic (169-150Ma) and Cretaceous (127-113Ma). They mostly belong to the high-K calc-alkaline series, and show strong enrichments in large ion lithophile elements (e.g., Cs, Rb, and K), depletions in Nb, Ta, and Ti, and negative Ba anomalies on primitive mantle-normalized diagrams. P2O5 contents decrease with increasing SiO2 content, and Th contents increase with increasing Rb content, consistent with the evolution trend of I-type magmas. These intrusions show a wide range of zircon eHf(t) values from -19.4 to 11.2, including in rocks with similar SiO2 contents, suggesting variable contributions from mantle and Qiangtang crustal sources. Fine-grained mafic to intermediate igneous enclaves in Jurassic intrusions have similar zircon U-Pb ages and similar or slightly higher zircon eHf(t) values to the host rocks, suggesting that the enclave magmas were derived from mixed magmas at depth and injected into more evolved magmas in upper crustal magma chambers. Magma mixing is also supported by the wide range of zircon Hf isotopic compositions (eHf(t)=-19.4 to 2.5) from within individual Jurassic and Cretaceous intrusions, and Jurassic enclaves. The Jurassic-Cretaceous magmas likely formed in a continental arc setting during subduction of the Bangong-Nujiang ocean between 170 and 110Ma, and evolved in the upper plate crust by MASH processes. © 2014 Elsevier B.V.